(untitled) (Bangladesh Journal of Botany, 2026)
In forage production, addressing the issues of yield fluctuations and unclear structural adaptability of Pennisetum purpureum caused by uneven water resource allocation, this paper employs multi-gradient irrigation control combined with anatomical analysis. By precisely regulating water supply and simultaneously analyzing the dynamic response of tissue structure, the morphological basis for high and stable yields of P. purpureum under water-saving conditions is effectively revealed. This article sets four irrigation levels of 100, 75, 50, and 25% ETc, and systematically monitors morphological parameters such as plant height, tiller number, stem thickness, leaf area index, and dry matter accumulation. Combined with the microstructure quantification of leaf and stem cross-sections, a four-dimensional evaluation system for WUE, morphological plasticity index, anatomical fitness, and yield structure coupling stability was constructed. WUE of P. purpureum is highest under 75% ETc treatment, and tillering ability was not inhibited but rather enhanced. Under 50% ETc conditions, the ratio of leaf palisade tissue/sponge tissue significantly increased, while the proportion of stem vascular bundles remained stable, indicating the synergistic optimization of photosynthesis and transport functions. The yield of hay is positively correlated with the proportion of stem thick walled cells (r>0.7), and this structural parameter fluctuates less than 10% under various water deficit treatments, confirming that it is a key anatomical guarantee for stable yield. The results indicate that P. purpureum can maintain forage productivity through morphological compensation and tissue restructuring under moderate water deficit, and has the potential to be promoted as a water-saving forage crop. Bangladesh J. Bot. 55(1): 133-143, 2026 (March)